Bacterial endocarditis in children: clinical and laboratory findings, and the role of echocardiography in its diagnosis and management - Sudigdo Sastroasmoro; Bambang Madiyono; Ismet N. Oesman; Sukman Tulus Putra (Paediatrica Indonesiana, 1989)
We report clinical and laboralory findings of 15 children with bacterial endocarditis, admitted ro the Department of Child Health, University of Indonesia/Cipto Mangunkusumo Hospital from February, 198710 June, 1989.There were 8 boys and 7 girls with bacterial endocarditis, ranging in age from 10 weeks 10 16 years. The diagnosis was suspected because of prolonged fever, with or without other manifestations, i.e. congestive heart failure, refractory anemia, or paroxysmal atrial tachycardia. The underlying heart disease was congenital in 12 cases and rheumatic heart disease in 3 cases.The clinical, electrocardiographic, and radiologic manifestations were generally predominated by the pre-existing heart disease. No characteristic findings of bacterial endocarditis, i.e. Osler's nodes, Janeway lesions or splinter haemorrhages were detected.Positive bacterial culture was obtained in 12 cases; the most frequent bacteria isolated was Pseudomonas aeruginosa (4 cases), Streptococcus viridans was isolated in 2 cases only.Vegetation was visualized echocardiographically in 12 cases; 9 with clear cut evidence of large vegetation, and the other 3 the vegetation was equivocal. On follow-up they disappeared gradually with clinical improvemenl. Large vegetation might need 2 full months 10 disappear echocardiographically.